Approach of Improved Topology Development Protocol In Ad Hoc Network Minimizing The Number of Hops and Maintaining Connectivity of Mobile Terminals Which Move From One To The Others - Lipur Sugiyanta (JAREE (Journal on Advanced Research in Electrical Engineering), 2017)
Wireless ad-hoc mesh network is a special kind of network, where all of the nodes move in time. Node is intended to help relaying packets of neighboring nodes using multi-hop routing mechanism in order to solve problem of dead communication. Wireless mesh network which engages broadcasting and contains multiple hops become increasingly vulnerable to problems such as routing problem and rapid increasing of overhead packets. During this progress, the delay on account of multi hop characteristics and redundant packets caused by communication nature potentially existed during communication. Typically, delay will increase in linearity with number of hops. There is a certain minimum level of delay that will be experienced due to the time it takes to transmit a packet through a link. Topology development holds a significant point prior to the data transmission. Without improved topology development protocol, this problem can decrease network’s performance in overall data transmission. We analyze the delay performance of a multi-hop wireless network with a dynamic route between each source and final destination pair. There are fluctuate interference constraints on the set of links that impose a fundamental delay performance of any instant network topology. At first, we present a similar Link State Routing network simulation to derive such referential lower bounds. We conduct extensive simulation studies to suggest that the average delay of multi-hop transmission policy can be made lower compared to the referential bound by using appropriate functions of network metrics. This paper provides a broadcast framework that engages various network metrics and at the same time maintaining connectivity of nodes (mobile terminals). The framework captures the essential features of the wireless network metrics, i.e. bandwidth, throughput, network buffer, direction, and round trip time. This research is useful since, in many cases, it find that the throughput is the most important parameter in reduction of delay transmission. This result is confirmed with another composite simulation result. Most of network hop delay is impacted with this composite metric, particularly in delay minimization on the longer hops. The reduction achievement on average delay by this algorithm is 0.577% and the total average delay reduction for this simulated network is 0.683%. This research will be further designed primarily for achieving maximum throughput in the multiple wireless network area. Keywords: multi-hop; delay; connectivity; metrics